Determinant of Sharing Value and Value Creation and Implications on Sale and Profits - Sembiring, Noor (International Journal of Economics and Financial Issues, 2018)
This study aims to (1) Know the influence of good relationships of customers, product attributes, and uniqueness of resources to shift values in the textile industry in West Java. (2) Knowing the influence of good relationships of customers, product attributes, and uniqueness of resources on value creation in the textile industry in West Java. (3) To know the relation between value shift and value creation in textile industry in West Java. (4) To know the effect of value shifts and value creation on sale in Textile industry in West Java. (5) To know the effect of value shifts and value creation on profit in Textile industry in West Java. (6) Knowing the relationship between sales with profit at Textile company in West Java. The method used is descriptive survey method and explanatory survey method, with sample 110 companies. Based on the results of the discussion, then obtained (1) Good relationship of customers, uniqueness of resources, and product attributes have a negative effect is not significant to the shift in value. When viewed partially, the uniqueness of dominant resources affects negatively on customer value shifts. (2) Good relationships of customers, sources of excellence, and product attributes have an effect on value creation. (3) The shift in value has a negative relationship of value creation. (4) The shift in value and value creation affects sales. (5) The shift in value and value creation affects the earnings. (6) Sales have a positive relationship of profit. Keywords: Good relationship with customers, product attributes, resource uniqueness, sharing value, value creation, sales, profit JEL Classification: M21, L67, O14